Financial crises and bank failures: a review of prediction methods - Yuliya Demyanyk; Iftekhar Hasan (Bank of Finland, 2009)
In this article we provide a summary of empirical results obtained in several economics and operations research papers that attempt to explain, predict, or suggest remedies for financial crises or banking defaults, as well as outlines of the methodologies used. We analyze financial and economic circumstances associated with the US subprime mortgage crisis and the global financial turmoil that has led to severe crises in many countries. The intent of the article is to promote future empirical research that might help to prevent bank failures and financial crises.
URN:NBN:fi:bof-20140807300
Keywords: 330